Current Concepts in Pediatric Robotic Assisted Pyeloplasty - Morales-López, Ramphis A.; Pérez-Marchán, Marcos; Pérez Brayfield, Marcos (Frontiers in Pediatrics, 2019)
Robotic surgery in pediatric urology has been gaining popularity since its introduction almost two decades ago. Robotic assisted pyeloplasty is the most commonly robotic procedure performed in pediatric urology. Advances in robotic technology, instrumentation, patient care and surgical expertise have allowed the correction of ureteropelvic junction (UPJ) obstruction in most patients using this minimally invasive technique. The excellent experience with robotic assisted pyeloplasty has challenged other approaches as a new gold standard for the treatment of UPJ obstruction. In this review, we will describe the technique as it relates to the different robotic platforms, review the surgical experience and compare its results to other surgical approaches. Also, we will discuss patient and parent satisfaction, cost and financial considerations, along with evaluating the future of robotic surgery in the treatment of UPJ obstruction.